Epidemiology of fishing related upper extremity injuries presenting to the emergency department in the United States. Issue 3 (3rd July 2018) - Gil, Joseph A.; Elia, Gregory; Shah, Kalpit N.; Owens, Brett D.; Got, Christopher
ABSTRACT: Objective : Fishing injuries commonly affect the hands. The goal of this study was to quantify the incidence of fishing-related upper extremity injuries that present to emergency departments in the United States. Methods : We examined the reported cases of fishing-related upper extremity injuries in the National Electronic Injury Surveillance System database. Analysis was performed based on age, sex and the type of injury reported. Results : The national incidence of fishing-related upper extremity injuries was 119.6 per 1 million person-years in 2014. The most common anatomic site for injury was the finger (63.3%), followed by the hand (20.3%). The most common type of injury in the upper extremity was the presence of a foreign body (70.4%). The incidence of fishing-related upper extremity injuries in males was 200 per 1 million person-years, which was significantly higher than the incidence in females (41 per 1 million person-years). Conclusion : The incidence of fishing-related upper extremity injuries that present to the Emergency Department was 120 per 1 million person-years. The incidence was significantly higher in males. With the widespread popularity of the activity, it is important for Emergency Physicians and Hand Surgeons to understand how to properly evaluate and manage these injuries.